The Role of Education and Income Inequality on Environmental Quality. A Panel Data Analysis of the EKC Hypothesis on OECD - Paolo Maranzano; Joao Paulo Cerdeira Bento; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2021)
We study the impact of human capital and the level of education on the pollution-income relationship controlling for income inequality in 17 OECD countries. By applying an innovative approach to country grouping, based on the temporal evolution of income inequality and clustering techniques to feature the annual value of the Gini Index on disposable income from 1987 to 2015, we have estimated panel data models by distinguishing between low and high levels of income inequality country clusters. Robustness checks and endogeneity tests are further performed considering as the discriminant factor the income inequality affecting the countries in the sample. The findings highlight the role of the educational level and years of schooling in validating the EKC hypothesis. We recommend that this variable should not be neglected in future EKC studies. Therefore, any EKC theory should also acknowledge a new EKC model specification that we named the Educational EKC.
Keywords: Q56; I24; I25; C51; C52; O15; O44; 330; Pollution-Income; Environmental Kunzets Curve; Education; Income-Inequality; Panel Data; Clustering